Diagnosis and management of nutrient constraints in grape - Brunetto, Gustavo (2019)
The yield and quality of grapes and by-products are dependent on the soil fertility and nutritional status. Thus, in acid soils and with low natural fertility, applications of acidity correctives and fertilizers are required. But, for example, fertilizer doses should be applied considering results of prediction criteria, as soil and tissue analysis, yield expectation, plant growth, and also the results of univariate methods (critical level and sufficiency range) or bivariate methods (diagnosis and recommendation integrated system and compositional nutrient diagnosis). In addition, fertilizers should be applied at the most appropriate times and modes, to avoid symptoms of deficiency or excess nutrients and soil contamination. Thus, in this chapter, we will focus on the main grapevine cultivars. We will also address the origin of excess and deficiency symptoms of nutrients, the criteria for fertilization, lime and gypsum application, and possible alternative methods to better estimate plant nutritional status. Lastly, we will report on the main management practices used to increase nutrient use in grapevines, thus reducing soil contamination of vineyards and surrounding areas.